Biotinidase Deficiency: Early Presentation - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1998)
Two infants with manifestations of biotinidase deficiency presenting at age 3 weeks and 2 weeks are reported from the University of Aarhus, Roskilde County Hospital, and Herning Central Hospital, Denmark.